2014
DOI: 10.1186/1476-9255-11-11
|View full text |Cite
|
Sign up to set email alerts
|

The effect of thiamine deficiency on inflammation, oxidative stress and cellular migration in an experimental model of sepsis

Abstract: BackgroundSepsis is a prevalent condition in critically ill patients and may be associated with thiamine deficiency (TD). The aim of this study was to evaluate the effect of TD on inflammation, oxidative stress and cellular recruitment in a sepsis model.MethodsThe experimental sepsis model, cecal ligation and puncture (CLP), was utilized on mice in comparison with a sham procedure. The following four groups were compared against each other: SHAM with AIN93G complete chow, SHAM with thiamine deficient (TD) chow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 48 publications
(52 reference statements)
2
28
0
1
Order By: Relevance
“…The present results indicated that the serum levels of inflammatory cytokines, biomarkers and inflammatory cells were upregulated in patients with sepsis compared with those in healthy individuals. Circulating inflammatory cytokines have been identified as mediators of damage in patients with sepsis (26). The present study reported the upregulation of the inflammatory cytokines IL-1, IL-17, TNF-α and IL-6 in sepsis patients compared with those in healthy individuals.…”
Section: Discussionsupporting
confidence: 47%
“…The present results indicated that the serum levels of inflammatory cytokines, biomarkers and inflammatory cells were upregulated in patients with sepsis compared with those in healthy individuals. Circulating inflammatory cytokines have been identified as mediators of damage in patients with sepsis (26). The present study reported the upregulation of the inflammatory cytokines IL-1, IL-17, TNF-α and IL-6 in sepsis patients compared with those in healthy individuals.…”
Section: Discussionsupporting
confidence: 47%
“…As suggested, the gut microbiota can establish efficient crosstalk with the rest of the body through a number of mediators. Interestingly, the metabolic end products of the [41,42] SCFAs [46] miRNAs [56] Indoxyl sulfate [43,44] NO [47] b Bile acids [50] TMAO [45] Vitamin K [51] N E [ 63] Oxalate [48,49] Vitamin B complex [17,[52][53][54] ANS [66,99] Serotonin [62] Threonine [55] ENS [67] GLP-1 [57] GLP-2 [58] PYY [59] GABA [60,61] ACh [65] Dopamine [64] H 2 S [87,88] a Some of these mediators have both pro-and anti-inflammatory effects…”
Section: The Gut Microbiota Regulates Inflammatory Processes Directlymentioning
confidence: 99%
“…The gut microbiota contributes to the health of the host by protective and trophic functions [6] in addition to aiding host metabolism by synthesizing conjugated linoleic acid [7], amino acids such as lysine [8], vitamin B complex [9], and vitamin K [10] and by facilitating the absorption of complex carbohydrates [11]. Additionally, the gut microbiota communicates with the rest of the body primarily via its interactions with the immune system [12] and its metabolic products, such as uremic toxins [2], oxalate [13], bile acids [14], short-chain fatty acids (SCFAs) [15], nitric oxide (NO) [16], vitamin K [10], vitamin B complex [17], threonine [18], microRNAs (miRNAs) [19], gut hormones [20], neurotransmitters [21], the autonomic nervous system (ANS), and the enteric nervous system (ENS) [22] and through effects on intestinal expression of cannabinoid receptor CB1 [23].…”
Section: Introductionmentioning
confidence: 99%
“…This result suggests that if P. aeruginosa relies solely on exogenous TPP for growth, the concentration should be higher than 25 µM. Reported TPP levels in mouse blood range from 0.3 to 1.2 µM, well below the TPP concentration sufficient to support growth of the thiL mutant (45,46). Consistent with these data, we found that the thiL mutant exhibited markedly reduced pathogenicity in a mouse infection model when compared with the wild-type strain (Figs 5-6).…”
Section: Discussionmentioning
confidence: 99%